Impact of ABO gene polymorphism and von Willebrand factor on genetic susceptibility to acute lymphoblastic leukemia in Egyptian pediatric patients - Elsayed I. Salim; Ahmed N. Shaaban; Amal K. Seleem; Zeinab I. Attia (Egyptian Journal of Medical Human Genetics)
Abstract Background Acute lymphoblastic leukemia (ALL) is the most common malignancy affecting children. The ABO blood group system and von Willebrand factor (VWF) have been associated with altering cancer risk, but few studies have examined their relationship with pediatric ALL. This study investigated the association between ABO gene polymorphism, VWF levels, ABO blood groups, and ALL risk in Egyptian pediatric patients. Methods Seventy-two ALL patients and 36 healthy controls were ABO phenotyped and genotyped for the ABO rs2519093 polymorphism using PCR–RFLP. VWF antigen levels were measured by ELISA. Results The CC genotype and C allele frequencies were significantly higher in ALL patients compared to controls (p < 0.001) and increased ALL risk by 12.94-fold and 7.63-fold, respectively. VWF levels were significantly higher in ALL patients versus controls overall (p = 0.006) and in the A, B, and O blood groups individually. After adjusting for VWF levels, the O, A, and B blood groups increased ALL risk 87.95-fold, 15.95-fold, and 8.77-fold, respectively, compared to AB. Conclusion The ABO C allele and O, A, and B blood groups are associated with increased pediatric ALL susceptibility in Egyptian patients, potentially through elevated VWF levels. These findings highlight ABO gene polymorphisms and blood groups as possible risk factors for ALL development.